The added value of family-centered rounds in the hospital setting: A systematic review of systematic reviews. - Josien M Woldring; Marie Louise Luttik; Wolter Paans; Reinold O B Gans (PLoS ONE, 2023)
Background Family engagement in care for adult inpatients may improve shared decision making in the hospital and the competence and preparedness of informal caregivers to take over the care at home. An important strategy to involve family members in hospital care processes is to include them in (ward) rounds, also called 'family-centered rounds'(FCRs). Objectives Summarize the evidence regarding the added value of FCRs from the perspectives of patients, family, and healthcare professionals. Methods A review protocol was registered a priori with PROSPERO (number CRD42022320915). The electronic databases PubMed, CINAHL, and PsycInfo were searched for English-written systematic reviews with a focus on FCRs. The results and methods were presented in line with the PRISMA guidelines, and the methodological quality of the included reviews was assessed using the adapted version of the AMSTAR tool. Results Of the 207 initial records, four systematic reviews were identified covering a total of 67 single studies, mainly performed in critical and pediatric care. Added values of FCR were described at review level, with references to single studies. All four systematic reviews reported an improvement in satisfaction among patients, family, and healthcare professionals, whereby satisfaction is linked to improved communication and interaction, improved situational understanding, inclusion of family in the decision-making process, and improved relationships within the care situation. Conclusion Although only limited research has been conducted on the value of FCRs in the adult non-critical care setting, and despite the existence of a variety of outcome measures, the results available from the pediatric and acute care setting are positive. The findings of the sole study in an adult non-critical patient population are in line with these results. Further research in adult non-critical care is required to verify its effects in this setting.